Transcriptome Analysis of Zygophyllum xanthoxylum Adaptation Strategies to Phosphate Stress - Hu, Xiaowei; Zhang, Lijing; Niu, Decao; Nan, Shuzhen; Wu, Shujuan; Gao, Hongjuan; Fu, Hua (Frontiers in Plant Science, 2021)
Soil phosphate (Pi) deficiency is a global issue and a major constraint on plant growth. Plants typically acclimatize to low Pi by enhancing their P utilization and/or P acquisition efficiencies; however, different species have variable preferred strategies. RNA sequencing analysis was performed on the shoots and roots of Zygophyllum xanthoxylum, under 1 day and 10 days of Pi stress, to investigate their adaptation strategies to P deprivation. A total of 364,614 unigenes and 9,270 differentially expressed genes (DEGs) were obtained via transcriptome sequencing. An analysis of the DEGs revealed that under the 10D treatment, anthocyanin synthesis genes were upregulated under Pi stress, whereas gibberellin, ethylene, and cytokinins synthesis genes were upregulated, and abscisic acid synthesis genes were downregulated. Genes related to organic acid synthesis, encoding for purple acid phosphatases (APase) and nucleases (RNase) were upregulated under the 1D and 10D treatments, respectively. Furthermore, genes associated with Pi transport were induced by Pi stress. Zygophyllum xanthoxylum has special P adaptation strategies, the variation trends of genes involved in external P mobilization and acquisition, which were different from that of most other species; however, the expression levels of organophosphorus mobilization related genes, such as APases and RNases, were significantly increased. Meanwhile, PHT2s and TPTs, which distributed Pi to effective sites (eg: chloroplast), played critical roles in the maintenance of photosynthesis. We speculated that these were economic and energy saving strategies, and there are critical adaptive mechanisms that Z. xanthoxylum employs to cope with deficits in Pi.